2009
DOI: 10.3892/ijo_00000373
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK-3β enhances reovirus-induced apoptosis in colon cancer cells

Abstract: Abstract. Reovirus functions as an oncolytic agent for many types of cancer including colon cancer. Although most studies have emphasized the role of activated Ras signaling in enhancing reoviral oncolysis in susceptible cells, we note that many colon cancers also display elevated ß-catenin. Thus, it is possible that enhanced ß-catenin may augment reoviral susceptibility in colon cancer cells. To explore this hypothesis, HEK293 cells were treated with the glycogen synthase kinase (GSK)-3ß inhibitor LiCl, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The effect of GSK-3β was thought to be independent of NF-κB [39]. Other authors found that inhibition of GSK-3β by LiCl reduced NF-κB activation, which accelerated caspase 8-mediated apoptosis [40]. In a study on colorectal cancer cells, it was reported that LiCl treatment reduced NF-κB levels and stimulated apoptosis in cells by affecting the B-cell lymphoma gene and other surviving genes [15].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of GSK-3β was thought to be independent of NF-κB [39]. Other authors found that inhibition of GSK-3β by LiCl reduced NF-κB activation, which accelerated caspase 8-mediated apoptosis [40]. In a study on colorectal cancer cells, it was reported that LiCl treatment reduced NF-κB levels and stimulated apoptosis in cells by affecting the B-cell lymphoma gene and other surviving genes [15].…”
Section: Discussionmentioning
confidence: 99%